Development of Teaching Materials for Writing Short Story Texts Based on the KBM (Community Can Write) Application by Asma Nadia and Isa Alamsyah in Creative Thinking Skills for Junior High School Students - Anita Rizkiyanti; Saifur Rahman; Fathiaty Murtadho (Dinasti Publisher, 2025)
This study aims to develop and evaluate a short story writing instructional material based on the